The Investigation of Zinc-Rich Paint (ZRP) Behavior in NaCl Solution by Electrochemical Methods - Azizul Helmi, Sofian; Kazuhiko, Noda (Springer, 2015)
Zinc-rich paints are coating materials designed to improve corrosion especially in marine and saline environments. Two types of zinc-rich paints (ZRPs) were employed in this research: 74 % ZRP and 96 % ZRP. The effectiveness of zinc coating systems has been analyzed in 0.5 M NaCl solution. Corrosion protections of coated metallic substrates were investigated using polarization measurement and electrochemical impedance spectroscopy (EIS). Electrochemical test showed that metallic substrates coated with 96 % ZRP have better corrosion resistance (galvanic protection) while those coated with 74 % ZRP have better barrier effect.